Carbon Sheet
A carbon sheet with controlled porosity enhances handling and processing of carbon nanotubes, enabling effective support of materials and improving electromagnetic wave and infrared absorption properties.
Patent Information
- Application Number
- JP2023048863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-09-28
- Filing Date
- 2023-03-24
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2038-09-27
Smart Images

Figure 0007619386000001 
Figure 0007619386000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon sheet and a method for producing the carbon sheet. Specifically, the present invention relates to a carbon sheet containing carbon nanotubes and a method for producing the same. [Background technology]
[0002] In recent years, carbon nanotubes (hereinafter sometimes referred to as "CNTs") have been attracting attention as a material that is lightweight and has excellent electrical conductivity, thermal conductivity, and mechanical properties.
[0003] Here, because CNTs have a large surface area, it has been proposed to support different materials on the surface of CNTs and use them as CNT composite materials that are endowed with other functions such as catalytic activity (see, for example, Patent Document 1).
[0004] On the other hand, CNTs are fine structures with nanometer-sized diameters, and therefore are difficult to handle and process when used alone. Therefore, it has been proposed to prepare a solution in which CNTs are dispersed, and then form the solution into a paper to assemble multiple CNTs into a film, which can then be used as a carbon nanotube film called "Buckypaper" (see, for example, Patent Document 2).
[0005] It has also been reported that a CNT sheet containing CNTs whose median length and aspect ratio are equal to or greater than a predetermined value, and arranged in a randomly oriented and uniformly distributed pattern, and whose CNT basis weight is equal to or greater than a predetermined value, can have electromagnetic wave absorption properties (see, for example, Patent Document 3).
[0006] Furthermore, it has been reported that an infrared absorbing member containing a CNT aggregate in which CNTs are aligned in the length direction can have high infrared absorptivity (see, for example, Patent Document 4). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2016 / 013245 [Patent Document 2] JP 2010-105909 A [Patent Document 3] Special Publication No. 2017-529298 [Patent Document 4] JP 2012-188305 A Summary of the Invention [Problem to be solved by the invention]
[0008] Here, the inventors conducted an investigation and found that when it is desired to support a different material on buckypaper in order to obtain a CNT composite material that is easy to handle and process, it is not possible to penetrate the different material into the interior of the buckypaper because the buckypaper is dense.
[0009] Therefore, an object of the present invention is to provide a material which is excellent in handleability and processability, and which is capable of supporting a different material to its inside when used as a support for a different material.
[0010] Furthermore, as a result of further investigations, the present inventors have found that when attempting to use the above-mentioned buckypaper as an electromagnetic wave absorbing material and / or an infrared absorbing material, the electromagnetic wave absorbing properties and infrared absorbing properties are insufficient. Therefore, an object of the present invention is to provide a material that has excellent electromagnetic wave absorption properties and infrared radiation absorption properties. [Means for solving the problem]
[0011] The present inventors have conducted extensive research with the aim of solving the above problems, and have found that a carbon sheet containing carbon nanotubes and having a porosity within a predetermined range is easy to handle and process, and is capable of supporting a different material to the inside when used as a support for a different material, thereby completing the present invention.
[0012] That is, the present invention aims to advantageously solve the above problems, and the carbon sheet of the present invention is characterized in that it contains carbon nanotubes and has a porosity of 5% to 90%. Thus, a carbon sheet containing carbon nanotubes and having a porosity within the above-mentioned range is easy to handle and process, and is capable of supporting a different material to the inside when used as a support for a different material. In the present invention, the porosity can be measured by mercury intrusion porosimetry.
[0013] Here, the carbon sheet of the present invention preferably comprises a carbon porous substrate and the carbon nanotubes attached to the porous substrate. By comprising a carbon porous substrate and carbon nanotubes attached to the porous substrate, the porosity inside the carbon sheet is increased, making it possible to support a larger amount of different materials inside the carbon sheet. In addition, the mechanical strength of the carbon sheet can be increased, making it possible to impart excellent processability.
[0014] The present inventors also discovered that a carbon sheet containing carbon nanotubes and having a porosity within a predetermined range has excellent electromagnetic wave absorption properties and infrared radiation absorption properties, and thus completed the present invention.
[0015] That is, the present invention aims to advantageously solve the above problems, and the carbon sheet of the present invention is characterized by including carbon nanotubes and having a porosity of 30% or more and 95% or less. Thus, a carbon sheet including carbon nanotubes and having a porosity within a predetermined range has excellent electromagnetic wave absorption properties and infrared absorption properties. In the present invention, the porosity can be measured by the method described in the Examples of this specification.
[0016] In the carbon sheet of the present invention, the carbon nanotubes are preferably single-walled carbon nanotubes, which can support a larger amount of different materials on the carbon nanotube surface and can further enhance the electromagnetic wave absorption property and infrared ray absorption property of the carbon sheet.
[0017] In the carbon sheet of the present invention, the nitrogen adsorption specific surface area of the carbon nanotubes is 600 m 2 / g or more. The nitrogen adsorption specific surface area is preferably 600 m 2 By using carbon nanotubes with a molecular weight of 100 / g or more, a larger amount of different materials can be supported on the carbon nanotube surface, and the electromagnetic wave absorption properties and infrared ray absorption properties of the carbon sheet can be further improved. In the present invention, the nitrogen adsorption specific surface area of carbon nanotubes can be measured according to the BET (Brunauer-Emmett-Teller) method using a fully automatic specific surface area measuring device (manufactured by Mountec Co., Ltd., product name "Macsorb (registered trademark) HM model-1210").
[0018] In addition, the carbon sheet of the present invention is preferably composed only of the carbon nanotubes. If the carbon sheet is composed only of carbon nanotubes, the carbon sheet can be made lighter. In addition, in an embodiment in which the carbon sheet is formed using only carbon nanotubes, the porosity of the carbon sheet can be adjusted by appropriately changing the conditions for dispersing the carbon nanotubes in a solvent or the like, thereby further improving the electromagnetic wave absorption property and infrared ray absorption property of the carbon sheet. Effect of the Invention
[0019] According to the present invention, it is possible to provide a carbon sheet which is excellent in handleability and processability, and which is capable of supporting a different material to the inside when used as a support for the different material. Furthermore, according to the present invention, a material having excellent electromagnetic wave absorption properties and infrared ray absorption properties can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, an embodiment of the present invention will be described in detail. The carbon sheet of the present invention is a carbon sheet that contains carbon nanotubes and has a void ratio and / or porosity within a predetermined range.
[0021] (Carbon sheet with defined porosity) The carbon sheet of the present invention, whose porosity is within a predetermined range, can be suitably used as a carrier for heterogeneous materials, such as metals such as tin, platinum, gold, and palladium, and metal oxides such as silicon oxide, lithium oxide, and lithium titanate. These heterogeneous materials can be in the form of particles having a size of 5 μm or less.
[0022] <Carbon sheet> The carbon sheet of the present invention contains carbon nanotubes, has a porosity within a predetermined range, and may optionally contain a carbon porous substrate. The carbon sheet of the present invention, whose porosity is within the above-mentioned predetermined range, is excellent in handleability and processability, and can be used as a carrier for a different material to support the different material to the inside. The carbon sheet of the present invention having a porosity within a predetermined range is a sheet containing only carbon. Here, the term "only carbon" in the above description does not exclude the presence of small amounts of impurities and other components other than carbon.
[0023] <<Structure of carbon sheet>> Specifically, the carbon sheet of the present invention, which has a porosity within a predetermined range, has, for example, (1) a structure in which only a plurality of carbon nanotubes are entangled so that the porosity is 5% or more and 90% or less, or (2) a structure in which carbon nanotubes are attached to a carbon porous substrate so that the porosity is 5% or more and 90% or less. The carbon sheet having the structure (1) above is lightweight and easy to handle. Furthermore, it can be suitably used as a carrier for different materials. On the other hand, the sheet having the structure (2) above can easily increase the porosity inside the carbon sheet by using a porous substrate, and can also increase the mechanical strength of the carbon sheet to give the carbon sheet excellent processability.
[0024] <<Characteristics of carbon sheet>> Furthermore, the carbon sheet preferably has the following properties:
[0025] [Porosity] The porosity of the carbon sheet of the present invention, which has a porosity within a predetermined range, must be 5% or more, preferably 40% or more, more preferably 48% or more, and even more preferably 70% or more. The porosity must be 90% or less, and is preferably 88% or less. If the porosity of the carbon sheet is 5% or more, the space inside the carbon sheet can be sufficiently secured, so that when the carbon sheet is used as a carrier for a different material, the different material can be well supported inside the carbon sheet. If the porosity is 90% or less, the self-supporting property of the carbon sheet can be sufficiently maintained, so that a carbon sheet with good handling and processability can be provided.
[0026] Thickness The thickness of the carbon sheet is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. The thickness of the carbon sheet is preferably 5000 μm or less, more preferably 4500 μm or less, and even more preferably 4000 μm or less. If the thickness of the carbon sheet is 2 μm or more, the strength of the obtained carbon sheet can be ensured. As a result, the processability of the carbon sheet can be improved. On the other hand, if the thickness of the carbon sheet is 5000 μm or less, the handleability of the obtained carbon sheet can be maintained good.
[0027] [density] The density of the carbon sheet is 0.01 g / cm 3 It is preferable that the concentration is 0.1 g / cm or more. 3 More preferably, it is 0.50 g / cm or more. 3 More preferably, it is 1.80 g / cm or more. 3 It is preferable that the density is 1.50 g / cm or less. 3 More preferably, it is 1.20 g / cm or less. 3 It is more preferable that the density of the carbon sheet is 0.01 g / cm or less. 3 If the density of the carbon sheet is 1.80 g / cm or more, the strength of the obtained carbon sheet can be ensured. As a result, the workability of the carbon sheet can be improved. 3 If it is equal to or less than this, a larger amount of different materials can be supported inside the carbon sheet. In the present invention, the "density of the carbon sheet" refers to the "bulk density" which can be calculated by measuring the mass, area and thickness of the carbon sheet and dividing the mass of the carbon sheet by the volume (area x thickness).
[0028] <<Carbon nanotubes>> The carbon nanotubes contained in the carbon sheet of the present invention are not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used, but the CNTs are preferably single-walled to five-walled CNTs, and more preferably single-walled CNTs. When single-walled CNTs are used, a larger amount of different materials can be supported on the carbon nanotube surface compared to when multi-walled CNTs are used.
[0029] The average diameter of the CNTs is preferably 0.5 nm or more, more preferably 1 nm or more, even more preferably 2 nm or more, preferably 15 nm or less, more preferably 10 nm or less, and even more preferably 5 nm or less. If the average diameter of the CNTs is 0.5 nm or more, sufficient space is secured between a plurality of CNTs when preparing a carbon sheet. Therefore, when the carbon sheet is used as a carrier for a different material, the different material can be well supported on the CNTs. In addition, if the average diameter of the CNTs is 15 nm or less, the physical properties such as the conductivity of the carbon sheet can be improved. The "average diameter of CNTs" can be determined by measuring the diameter (outer diameter) of 100 randomly selected CNTs using a transmission electron microscope. The average diameter of CNTs may be adjusted by changing the manufacturing method or manufacturing conditions of CNTs, or by combining multiple types of CNTs obtained by different manufacturing methods.
[0030] The aspect ratio (length / diameter) of the CNTs is preferably greater than 10. The aspect ratio of the CNTs can be determined by measuring the diameter and length of 100 randomly selected CNTs using a transmission electron microscope and calculating the average value of the ratio of the diameter to the length (length / diameter).
[0031] Here, the nitrogen adsorption specific surface area of CNT is 600 m 2 / g or more, and 2 / g or more is more preferable, and 1000m 2 / g or more. The nitrogen adsorption specific surface area of CNTs is preferably 2500 m 2 / g or less, and 2 It is more preferable that the nitrogen adsorption specific surface area of the CNT is 600 m 2 / g or more, it is possible to support a larger amount of different materials on the carbon nanotube surface in the carbon sheet. 2 If the carbon nanotube size is 1 / g or less, excessive crowding of the CNTs can be suppressed, and when the carbon sheet is used as a support for a different material, the different material can be favorably supported on the CNTs.
[0032] CNTs having the above-mentioned properties can be efficiently manufactured, for example, by a method (super-growth method; see International Publication No. 2006 / 011655) in which, when a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for producing carbon nanotubes on its surface and CNTs are synthesized by chemical vapor deposition (CVD), a trace amount of an oxidizing agent (catalyst activation material) is made present in the system to dramatically improve the catalytic activity of the catalyst layer. Note that, hereinafter, carbon nanotubes obtained by the super-growth method may be referred to as "SGCNTs."
[0033] <<Porous carbon substrate>> The carbon porous substrate is composed solely of carbon material. In the above description, the term "only" does not exclude the presence of small amounts of impurities or other components other than the carbon material. The carbon porous substrate is not particularly limited, and examples thereof include graphite, woven or nonwoven carbon fiber fabric, and carbon paper. These may be used alone or in combination of two or more.
[0034] The porosity of the carbon porous substrate is not particularly limited, but from the viewpoint of increasing the porosity of the produced carbon sheet, it is preferably 5% or more, more preferably 40% or more, and even more preferably 70% or more. Also, the porosity is preferably 90% or less.
[0035] <Manufacturing method of carbon sheets with specified porosity> The method for producing the carbon sheet of the present invention described above is not particularly limited, but for example, a method for producing a carbon sheet having the structure (1) above may be the following method 1), and a method for producing a carbon sheet having the structure (2) above may be the following method 2). 1) A method in which a primary sheet is obtained by removing a solvent from a dispersion containing CNTs, spacer particles, and a solvent, and then the spacer particles are removed from the primary sheet; 2) A method in which a dispersion containing CNTs and a solvent is impregnated into a porous carbon substrate, and then the solvent is removed; From the viewpoint of reducing the weight of the carbon sheet, it is preferable to use the above method 1), which can obtain a carbon sheet composed only of CNTs. On the other hand, from the viewpoint of supporting a larger amount of heterogeneous materials inside the carbon sheet, it is preferable to use the method 2) above, which has a porous carbon substrate and CNTs attached to the porous substrate, thereby obtaining a carbon sheet with an even higher porosity.
[0036] <<Carbon sheet manufacturing method 1)>> In detail, the carbon sheet manufacturing method 1) includes a step of removing the solvent from a dispersion liquid containing CNTs, spacer particles, and a solvent to obtain a primary sheet containing CNTs and spacer particles (primary sheet preparation step), and a step of removing the spacer particles from the primary sheet (spacer particle removal step).
[0037] [Primary sheet preparation process] In the primary sheet preparation step, a primary sheet containing the carbon nanotubes and the spacer particles is obtained by removing the solvent from a dispersion containing the carbon nanotubes, the spacer particles, and the solvent.
[0038] -Dispersion- The dispersion liquid used for preparing the primary sheet is not particularly limited, and a dispersion liquid obtained by dispersing an aggregate of CNTs and spacer particles in a solvent using a known dispersion treatment method can be used. Specifically, the dispersion liquid can be a dispersion liquid containing CNTs, spacer particles, and a solvent, and optionally further containing a dispersion additive such as a dispersant.
[0039] --Components in the dispersion liquid-- As the CNTs, the CNTs mentioned above in the section "Carbon Sheet" can be used.
[0040] There are no particular limitations on the spacer particles, so long as they disperse well in the dispersion liquid and can be efficiently removed in the spacer particle removal step. Examples of the types of spacer particles include carbon black, glass particles, titanium oxide particles, aluminum oxide particles, resin particles, etc. When the spacer particle removal step is performed by a heat treatment, it is preferable to use resin particles, and it is more preferable to use hollow resin particles, from the viewpoint of efficiently removing the spacer particles by heating. Furthermore, specific examples of resins used in the resin particles include plastics (polyethylene, polypropylene, polystyrene, ABS resin, methacrylic resin, polyvinyl chloride, polyamide, polyacetal, polycarbonate, polybutylene terephthalate, polyethylene terephthalate, polyphenylene oxide, polyamideimide, polyether ether ketone, polyphenylene sulfide, polytetrafluoroethylene, phenolic resin, urea resin, melamine resin, unsaturated polyester resin, epoxy resin, etc.), synthetic rubber (isoprene rubber, butadiene rubber, styrene-butadiene rubber, chloroprene rubber, nitrile rubber, polyisobutylene rubber, ethylene propylene rubber, chlorosulfonated polyethylene, acrylic rubber, fluororubber, epichlorohydrin rubber, urethane rubber, silicone rubber, etc.), and natural rubber. These may be used alone or in combination of two or more.
[0041] In addition, the particle size of the spacer particles is not particularly limited as long as it does not prevent the primary sheet and the carbon sheet from forming a sheet shape, but it is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 100 nm or more, and is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 600 nm or less.
[0042] The solvent for the dispersion (the dispersion medium for the CNTs and the spacer particles) is not particularly limited, and examples thereof include water; alcohols such as methanol, ethanol, n-propanol, isopropanol (isopropyl alcohol), n-butanol, isobutanol, t-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, and amyl alcohol; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; ethers such as diethyl ether, dioxane, and tetrahydrofuran; amide-based polar organic solvents such as N,N-dimethylformamide and N-methylpyrrolidone; aromatic hydrocarbons such as toluene, xylene, chlorobenzene, orthodichlorobenzene, and paradichlorobenzene; and the like. These may be used alone or in combination of two or more.
[0043] Furthermore, additives for dispersions that are optionally blended in the dispersions are not particularly limited, and examples thereof include additives that are generally used in the preparation of dispersions, such as dispersants. In addition, from the viewpoint of preventing clogging of filter paper when removing the solvent from the dispersion by filtration, for example, and from the viewpoint of suppressing deterioration of the physical properties (e.g., electrical conductivity) of the obtained carbon sheet, it is preferable to add a small amount of dispersion additives such as dispersants.
[0044] The dispersant used to prepare the dispersion liquid is not particularly limited as long as it can disperse the CNTs and spacer particles and can be dissolved in the above-mentioned solvent, and a surfactant, a synthetic polymer, or a natural polymer can be used.
[0045] Examples of the surfactant include sodium dodecylsulfonate, sodium deoxycholate, sodium cholate, and sodium dodecylbenzenesulfonate. Examples of synthetic polymers include polyether diols, polyester diols, polycarbonate diols, polyvinyl alcohol, partially saponified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, acetal group-modified polyvinyl alcohol, butyral group-modified polyvinyl alcohol, silanol group-modified polyvinyl alcohol, ethylene-vinyl alcohol copolymers, ethylene-vinyl alcohol-vinyl acetate copolymer resins, dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, acrylic resins, epoxy resins, modified epoxy resins, phenoxy resins, modified phenoxy resins, phenoxy ether resins, phenoxy ester resins, fluorine-based resins, melamine resins, alkyd resins, phenolic resins, polyacrylamides, polyacrylic acids, polystyrene sulfonic acids, polyethylene glycols, and polyvinylpyrrolidone. Further, examples of natural polymers include polysaccharides such as starch, pullulan, dextran, dextrin, guar gum, xanthan gum, amylose, amylopectin, alginic acid, gum arabic, carrageenan, chondroitin sulfate, hyaluronic acid, curdlan, chitin, chitosan, and cellulose, as well as salts or derivatives thereof. These dispersants can be used alone or in combination of two or more.
[0046] --Dispersion liquid properties-- The concentration of CNT in the dispersion liquid is preferably 0.001% by mass or more and 5% by mass or less, depending on the type of CNT. If the concentration of CNT is less than 0.001% by mass, the amount of carbon sheet obtained by removing the solvent and spacer particles is small, and there is a risk that the production efficiency cannot be sufficiently improved. In addition, if the concentration of CNT is more than 5% by mass, there is a risk that the dispersibility of CNT in the dispersion liquid decreases, and the viscosity of the dispersion liquid increases, decreasing the flowability.
[0047] --Preparation of dispersion-- The dispersion liquid can be prepared using known dispersion processing methods such as dispersion processing by ultrasonication, dispersion processing by a jet mill, dispersion processing by high shear stirring, and dispersion processing using the product name "BERYU SYSTEM PRO" (manufactured by BERYU Co., Ltd.).
[0048] The addition of spacer particles to the dispersion liquid can be performed at any time without any particular limitation as long as the desired effect can be obtained. For example, the spacer particles can be added when the CNTs are added to the solvent to prepare the crude dispersion liquid.
[0049] -Removal of solvent- The method for removing the solvent from the dispersion is not particularly limited, and known solvent removal methods such as drying and filtration can be used. Among them, from the viewpoint of efficiently removing the solvent, it is preferable to use reduced pressure drying, vacuum drying, or filtration as the solvent removal method. Furthermore, from the viewpoint of easily and quickly removing the solvent, it is preferable to use filtration as the solvent removal method, and it is even more preferable to use reduced pressure filtration. If the solvent is removed quickly and efficiently, it is possible to suppress the re-aggregation of the CNTs and spacer particles that have been dispersed once, and to suppress uneven density of the obtained carbon sheet. Here, it is not necessary to completely remove the solvent from the dispersion. As long as the CNTs and spacer particles remaining after the solvent has been removed are in a state that allows them to be handled as an aggregate (primary sheet), it is not a problem if some solvent remains.
[0050] [Spacer particle removal process] In the spacer particle removing step, the spacer particles are removed from the primary sheet obtained in the above-mentioned primary sheet preparing step, thereby obtaining a carbon sheet. The method for removing the spacer particles from the primary sheet described above is not particularly limited, and any known method for removing spacer particles from a substrate can be used. Specific examples include a method of applying a physical impact to the primary sheet to cause the spacer particles to detach, a method of removing the spacer particles by heat treatment, etc. Among these, the method of removing the spacer particles by heat treatment is preferred from the viewpoint of more efficiently removing the spacer particles and increasing the porosity inside the carbon sheet. When the heat treatment method is used, the spacer particles used are preferably made of a material that can be easily removed by heat treatment, such as hollow resin particles.
[0051] It is not necessary to completely remove the spacer particles from the primary sheet, and there is no problem if a small amount of spacer particles remain as long as the performance of the carbon sheet obtained after removal of the spacer particles is not affected.
[0052] <<Carbon sheet manufacturing method 2)>> Specifically, carbon sheet manufacturing method 2) comprises a step of impregnating a carbon porous substrate with a dispersion containing CNTs and a solvent (dispersion impregnation step), and a step of removing the solvent from the dispersion impregnated porous substrate (solvent removal step). Moreover, the manufacturing method 2) may optionally comprise a cleaning step once or multiple times before and / or after the solvent removal step. And, when the cleaning step is carried out after the solvent removal step, the solvent removal step may be carried out again after the cleaning step. Furthermore, in carbon sheet manufacturing method 2), the cleaning step and the solvent removal step may be carried out repeatedly multiple times.
[0053] [Dispersion liquid impregnation process] In the dispersion impregnation step, a dispersion containing CNTs and a solvent is impregnated into a carbon porous substrate to obtain the dispersion-impregnated porous substrate.
[0054] -Dispersion- The dispersion liquid used in the dispersion liquid impregnation step is not particularly limited, and a dispersion liquid obtained by dispersing an aggregate of CNTs in a solvent using a known dispersion treatment method can be used. Specifically, the dispersion liquid can be a dispersion liquid containing CNTs and a solvent, and optionally further containing a dispersion liquid additive such as a dispersant.
[0055] --Components of the dispersion liquid-- The CNTs, solvent, and additives for the dispersion liquid used in the dispersion liquid may be the same as those usable in the dispersion liquid used in the above-mentioned carbon sheet manufacturing method 1). The properties and preparation method of the dispersion liquid may also be the same as those of the dispersion liquid used in the above-mentioned carbon sheet manufacturing method 1).
[0056] -Porous carbon substrate- As the carbon porous substrate used in the dispersion liquid impregnation step, the carbon porous substrate described above in the section "Carbon sheet" can be used.
[0057] - A method for impregnating a porous carbon substrate with a dispersion liquid - The method of impregnating the porous carbon substrate with the dispersion liquid is not particularly limited as long as the porous substrate can be uniformly impregnated with the dispersion liquid, and any known method can be used. Specifically, the method includes a method of applying the dispersion liquid onto the porous substrate, a method of spraying the dispersion liquid onto the porous substrate, and a method of immersing the porous substrate in the dispersion liquid.
[0058] [Solvent removal process] In the solvent removal step, the solvent is removed from the dispersion-impregnated porous substrate to obtain a carbon sheet. The method for removing the solvent from the dispersion-impregnated porous substrate is not particularly limited, and known solvent removal methods such as drying can be used. Among them, from the viewpoint of efficiently removing the solvent, it is preferable to use reduced pressure drying or vacuum drying as the solvent removal method. If the solvent is efficiently removed, it is possible to suppress re-aggregation of the CNTs once dispersed, and to suppress uneven density of the obtained carbon sheet.
[0059] [Cleaning process] The carbon sheet manufacturing method 2) may optionally comprise one or more washing steps before and / or after the above-mentioned solvent removal step. In the washing step, the dispersion-impregnated porous substrate obtained in the dispersion impregnation step or the carbon sheet obtained in the solvent removal step is washed to remove the dispersant derived from the dispersion from the dispersion-impregnated porous substrate or the carbon sheet.
[0060] A specific washing method is not particularly limited, and any known washing method can be used as long as it can properly remove the dispersant from the dispersion-impregnated porous substrate or carbon sheet and does not cause the CNTs attached to the carbon porous substrate to be detached. Specific examples of the washing method include a method of rinsing the dispersion-impregnated porous substrate or carbon sheet with a washing liquid, and a method of immersing the dispersion-impregnated porous substrate or carbon sheet in a washing liquid.
[0061] The cleaning liquid used in the above-mentioned cleaning step is not particularly limited, and for example, the solvent of the above-mentioned dispersion liquid can be used as the cleaning liquid. It is not necessary to completely remove the dispersant contained in the dispersion-impregnated porous substrate or carbon sheet, and there is no problem if the dispersant remains within a range in which the desired effect can be obtained.
[0062] (Carbon sheet with specified porosity) The carbon sheet of the present invention, whose porosity is within a predetermined range, can exhibit excellent electromagnetic wave absorbing properties, and can therefore be suitably used as an electromagnetic wave absorbing material for use in electronic devices and communication devices, etc. Furthermore, the carbon sheet of the present invention, whose porosity is within a predetermined range, can exhibit excellent infrared absorbing properties, and can therefore be suitably used as an infrared absorbing material for use in heat insulation sheets, etc.
[0063] <Carbon sheet> The carbon sheet of the present invention contains carbon nanotubes and has a porosity within a predetermined range, and therefore has excellent electromagnetic wave absorption properties and infrared absorption properties. The carbon sheet of the present invention having a porosity within a predetermined range is a sheet containing only carbon. Here, "only carbon" in the above description does not exclude the presence of a small amount of impurities or other components other than carbon.
[0064] <<Structure of carbon sheet>> Specifically, the carbon sheet of the present invention, which has a porosity within a predetermined range, has, for example, (3) a structure in which only a plurality of carbon nanotubes are entangled so that the porosity is 30% or more and 95% or less.
[0065] <<Characteristics of carbon sheet>> Furthermore, the carbon sheet preferably has the following properties:
[0066] [Porosity] The porosity of the carbon sheet of the present invention, which has a porosity within a predetermined range, must be 30% or more, preferably 35% or more, and more preferably 40% or more. The porosity must be 95% or less, preferably 94% or less, and more preferably 93% or less. When the porosity of the carbon sheet is 30% or more, the electromagnetic wave absorption property and infrared absorption property of the carbon sheet can be further improved. When the porosity is 95% or less, the self-supporting property of the carbon sheet can be sufficiently maintained, and therefore, a carbon sheet with good handling and processability can be provided.
[0067] [Porosity] The carbon sheet of the present invention may have a porosity within the above-mentioned predetermined range and at the same time may have the predetermined porosity described above in the section "Carbon sheet with specified porosity". That is, the porosity in the carbon sheet of the present invention having a porosity within the predetermined range may be within the predetermined range described above in the section "Carbon sheet with specified porosity". Specifically, the porosity of the carbon sheet of the present invention, which has a porosity within a predetermined range, is preferably 5% or more, more preferably 40% or more, even more preferably 48% or more, and even more preferably 70% or more. The porosity is preferably 90% or less, and more preferably 88% or less. If the porosity of the carbon sheet is 5% or more, the space inside the carbon sheet can be sufficiently secured, so that when the carbon sheet is used as a carrier for a different material, the different material can be well supported inside the carbon sheet. If the porosity is 90% or less, the self-supporting property of the carbon sheet can be sufficiently maintained, so that a carbon sheet with good handling and processability can be provided.
[0068] Thickness The thickness of the carbon sheet is preferably 2 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. The thickness of the carbon sheet is preferably 5000 μm or less, more preferably 4500 μm or less, and even more preferably 4000 μm or less. If the thickness of the carbon sheet is 2 μm or more, the strength of the obtained carbon sheet can be ensured. As a result, the processability of the carbon sheet can be improved. On the other hand, if the thickness of the carbon sheet is 5000 μm or less, the handleability of the obtained carbon sheet can be maintained good.
[0069] [density] The density of the carbon sheet is 0.01 g / cm 3 It is preferable that the concentration is 0.1 g / cm or more. 3 More preferably, it is 0.50 g / cm or more. 3 More preferably, it is 1.80 g / cm or more. 3 It is preferable that the density is 1.50 g / cm or less. 3 More preferably, it is 1.20 g / cm or less. 3 It is more preferable that the density of the carbon sheet is 0.01 g / cm or less. 3If the density of the carbon sheet is 1.80 g / cm or more, the strength of the obtained carbon sheet can be ensured. As a result, the workability of the carbon sheet can be improved. 3 If it is less than this, the electromagnetic wave absorption property and infrared ray absorption property of the carbon sheet can be further improved. In the present invention, the "density of the carbon sheet" refers to the "bulk density" which can be calculated by measuring the mass, area and thickness of the carbon sheet and dividing the mass of the carbon sheet by the volume (area x thickness).
[0070] <<Carbon nanotubes>> The carbon nanotubes contained in the carbon sheet of the present invention are not particularly limited, and single-walled carbon nanotubes and / or multi-walled carbon nanotubes can be used, but the CNTs are preferably single-walled to five-walled CNTs, and more preferably single-walled CNTs. The use of single-walled CNTs can further improve the electromagnetic wave absorption properties and infrared absorption properties of the carbon sheet compared to the use of multi-walled CNTs.
[0071] The average diameter of the CNTs is preferably 0.5 nm or more, more preferably 1 nm or more, even more preferably 2 nm or more, preferably 15 nm or less, more preferably 10 nm or less, and even more preferably 5 nm or less. If the average diameter of the CNTs is 0.5 nm or more, sufficient space is secured between the multiple CNTs when preparing the carbon sheet. Also, if the average diameter of the CNTs is 15 nm or less, the physical properties such as electromagnetic wave absorption properties, infrared absorption properties, and electrical conductivity of the carbon sheet can be improved. The "average diameter of CNTs" can be determined by measuring the diameter (outer diameter) of 100 randomly selected CNTs using a transmission electron microscope. The average diameter of CNTs may be adjusted by changing the manufacturing method or manufacturing conditions of CNTs, or by combining multiple types of CNTs obtained by different manufacturing methods.
[0072] The aspect ratio (length / diameter) of the CNTs is preferably greater than 10. The aspect ratio of the CNTs can be determined by measuring the diameter and length of 100 randomly selected CNTs using a transmission electron microscope and calculating the average value of the ratio of the diameter to the length (length / diameter).
[0073] Here, the nitrogen adsorption specific surface area of CNT is 600 m 2 / g or more, and 2 / g or more is more preferable, and 1000m 2 / g or more. The nitrogen adsorption specific surface area of CNTs is preferably 2500 m 2 / g or less, and 2 When the nitrogen adsorption specific surface area of the CNT is in the above range, the electromagnetic wave absorption property and infrared ray absorption property of the carbon sheet can be further improved.
[0074] CNTs having the above-mentioned properties can be efficiently manufactured, for example, by a method (super-growth method; see International Publication No. 2006 / 011655) in which, when a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for producing carbon nanotubes on its surface and CNTs are synthesized by chemical vapor deposition (CVD), a trace amount of an oxidizing agent (catalyst activation material) is made present in the system to dramatically improve the catalytic activity of the catalyst layer. Note that, hereinafter, carbon nanotubes obtained by the super-growth method may be referred to as "SGCNTs."
[0075] <Manufacturing method of carbon sheet with specified porosity> The method for producing the carbon sheet of the present invention described above is not particularly limited, but from the viewpoint of producing a carbon sheet having a porosity within the above-mentioned predetermined range, for example, the following method 3) is preferable. 3) A method in which CNTs are dispersed in a solvent and the solvent is then removed from the resulting dispersion.
[0076] <<Carbon sheet manufacturing method 3)>> The carbon sheet manufacturing method 3) specifically includes a step of dispersing CNTs in a solvent to obtain a dispersion (a dispersion preparation step), and a step of removing the solvent from the dispersion (a solvent removal step).
[0077] [Dispersion liquid preparation process] In the dispersion preparation step, CNTs are dispersed in a solvent to obtain a CNT dispersion.
[0078] Here, as the CNTs, the CNTs described above in the section "Carbon sheet" can be used. As the solvent, the solvents mentioned above as usable in the carbon sheet manufacturing method 1) can be used.
[0079] The method for dispersing CNTs in a solvent is not particularly limited, and known dispersion methods such as dispersion treatment using ultrasound, dispersion treatment using a jet mill, dispersion treatment using high shear stirring, and dispersion treatment using a product called "BERYU SYSTEM PRO" (manufactured by Biryu Co., Ltd.) can be used.
[0080] The CNTs in the obtained CNT dispersion are usually present in the form of bundles, which are collections of multiple CNTs. Here, the average bundle diameter of the CNTs can be adjusted by appropriately changing the method and conditions of the above-mentioned dispersion treatment. The average bundle diameter of the CNTs in the CNT dispersion is preferably 0.5 μm or more, preferably 1000 μm or less, and more preferably 100 μm or less. If the average bundle diameter of the CNTs in the CNT dispersion is 0.5 μm or more, the porosity of the carbon sheet to be manufactured can be sufficiently increased. On the other hand, if the average bundle diameter of the CNTs in the CNT dispersion is 1000 μm or less, the porosity of the carbon sheet to be manufactured can be suppressed from being excessively increased. Therefore, if the average bundle diameter of the CNTs dispersed in the solvent is within the above-mentioned predetermined range, the porosity of the carbon sheet to be manufactured can be easily kept within the above-mentioned predetermined range. The average bundle diameter of CNTs can be measured by the method described in the Examples of this specification.
[0081] [Solvent removal process] In the solvent removal step, the solvent is removed from the CNT dispersion to obtain a carbon sheet. As a method for removing the solvent from the dispersion, the methods mentioned above as usable in the solvent removal step in the carbon sheet production method 1) can be used. EXAMPLES
[0082] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the examples and comparative examples, the self-supporting ability, electrical conductivity, porosity, air permeability, thickness, density (bulk density), porosity, electromagnetic wave absorption properties, and infrared absorption properties of the carbon sheet, as well as the average bundle diameter of the CNTs, were evaluated using the following methods.
[0083] <Self-supporting carbon sheet> The produced carbon sheets were visually inspected to see whether they maintained their film state by themselves, and their self-supporting ability was evaluated according to the following criteria. A: A single membrane that maintains its membrane state (self-supporting). B: A single membrane that does not maintain its membrane state (not self-supporting).
[0084] <Conductivity> The electrical conductivity of the prepared carbon sheet was measured by a four-probe method (manufactured by Mitsubishi Chemical Analytech, product name "Lorestar GX").
[0085] <Porosity> The porosity of the produced carbon sheets was measured by mercury intrusion porosimetry (Shimadzu Corporation, Autopore IV9510).
[0086] <Breathability> The prepared carbon sheets were measured for air permeability by the Frazier method and evaluated according to the following criteria: Air permeability of 5 cc / cm 2 / s or more 60cc / cm2 If it is 5 cc / cm or less, when using the carbon sheet as a carrier for a different material, the different material can be well supported up to the inside of the carbon sheet. On the other hand, if the air permeability is less than 5 cc / cm 2 / s, the different material cannot be supported up to the inside of the carbon sheet, and if the air permeability exceeds 60 cc / cm 2 / s, the mechanical strength of the carbon sheet decreases. A: The air permeability is 5 cc / cm or more and 60 cc / cm 2 / s or less. 2 / s or less. B: The air permeability is less than 5 cc / cm 2 / s or exceeds 60 cc / cm 2 / s.
[0087] <Thickness, density (bulk density), and porosity> The prepared carbon sheet was cut into a 1 cm square, and the thickness of the obtained test piece was measured using a micrometer (Mitutoyo Corporation's "Digital Standard Outer Micrometer"), and this was taken as the thickness of the carbon sheet. Furthermore, the mass (g) of the test piece was measured, and the density (bulk density) of the carbon sheet was calculated by the following formula (1). Bulk density of carbon sheet (g / cm 3 ) = mass of test piece (g) / {1 cm 2 × thickness of test piece (cm)} ··· (1) Then, using the obtained bulk density, the porosity of the carbon sheet was calculated by the following formula (2). Porosity = [1 - {bulk density of carbon sheet (g / cm 3 ) / 1.3}] × 100 ··· (2) Note that "1.3" in formula (2) refers to the true density of carbon (g / cm 3 ).
[0088] <Average bundle diameter of CNT> The obtained dispersion was applied to a silicon substrate, and bundles of multiple CNTs were observed using a scanning electron microscope (SEM; "JSM-7800F Prime" manufactured by JEOL Ltd.) The bundle diameters of 100 randomly selected bundles were measured, and the average value was taken as the average bundle diameter of the CNTs.
[0089] <Electromagnetic wave absorption characteristics> The electromagnetic wave absorption (dB) of the carbon sheet was measured in the millimeter wave band (W-Band: 60GHz to 120GHz) by the free space method. From the results of the electromagnetic wave absorption at 80GHz and 110GHz, the electromagnetic wave absorption properties of the carbon sheet were evaluated according to the following criteria. A: Electromagnetic wave absorption is 5dB or more B: Electromagnetic wave absorption is less than 5 dB
[0090] <Infrared absorption characteristics> The infrared absorption amount (%) of the produced carbon sheet in the range of 3 μm to 15 μm was measured by total reflectance measurement using an integrating sphere, and the infrared absorption properties of the carbon sheet were evaluated according to the following criteria. A: Infrared absorption is 90% or more B: Infrared absorption is less than 90%
[0091] (Example 1-1) <Preparation of carbon sheets> CNT (manufactured by Zeon Nano Technology, product name "ZEONNANO (registered trademark) SG101", SGCNT mainly containing single-walled CNT, average diameter: 3.3 nm, nitrogen adsorption specific surface area: 1,000 m 2400 mg of CNTs (CNTs / g or more) and 100 mg of hollow latex (Nipol MH5055, average particle size: 500 nm, manufactured by Zeon Corporation) as spacer particles were weighed out and mixed into 2 L of methyl ethyl ketone as a solvent and stirred for 2 minutes with a homogenizer to obtain a crude dispersion. Using a wet jet mill (JN-20, manufactured by Jokou Corporation), the crude dispersion was passed through a 0.5 mm flow path of the wet jet mill at a pressure of 100 MPa for two cycles to disperse the CNTs in methyl ethyl ketone, obtaining dispersion A. The obtained dispersion A was filtered under reduced pressure using Kiriyama filter paper (No. 5A) to obtain a primary sheet. The obtained primary sheet was heat-treated at 350°C for 12 hours to remove the hollow latex particles, and the thickness was 100 μm and the density was 1.15 g / cm 3 A carbon sheet having the formula: The obtained carbon sheet was evaluated for its self-supporting property, electrical conductivity, porosity, and air permeability. The results are shown in Table 1.
[0092] <Preparation of metal oxide-supported sheet> A solution of 2 g of titanium (IV) butoxide (manufactured by Wako Pure Chemical Industries) and 20 g of isopropyl alcohol was prepared, and the prepared carbon sheet 20 mm square was immersed in the solution and treated for 10 minutes with a planetary mill (Thinky's Awatori Rentaro AR-100). Then, a solution of 0.5 g of lithium acetate (manufactured by Tokyo Chemical Industry Co., Ltd.), 1 g of acetic acid, 1 g of pure water, and 3 g of isopropyl alcohol was added and further treated for 10 minutes, after which the prepared carbon sheet was taken out and dried under reduced pressure at 80°C for 10 hours, and then heat-treated at 400°C in a nitrogen atmosphere to obtain a carbon sheet carrying a metal oxide (metal oxide-supported sheet). A cross section of the prepared metal oxide-supported sheet was cut out with a cryomicrotome, and the cross section was observed with a scanning electron microscope, confirming that a metal oxide with an average diameter of 27 nm was supported on the surface of the sheet.
[0093] (Examples 1-2 and 1-3) Carbon sheets were prepared in the same manner as in Example 1, except that the amount of spacer particles added was changed to give the porosity of the carbon sheet the value shown in Table 1, and the same items were evaluated. The results are shown in Table 1. Furthermore, a metal oxide-supporting sheet was produced by carrying out the same treatment as in Example 1, and the average diameter of the metal oxide was measured. The results are shown in Table 1.
[0094] (Examples 1 to 4) CNT (manufactured by Zeon Nano Technology, product name "ZEONNANO (registered trademark) SG101", SGCNT mainly containing single-walled CNT, average diameter: 3.3 nm, nitrogen adsorption specific surface area: 1,000 m 2 / g or more) was weighed out and mixed into 500 mL of a 1 mass % aqueous solution of sodium dodecylbenzenesulfonate (SDBS) as a solvent containing a dispersant, to obtain a crude dispersion. The obtained crude dispersion was filled into a high-pressure homogenizer (manufactured by Beryu Co., Ltd., product name "BERYU SYSTEM PRO") equipped with a multi-stage pressure control device (multi-stage pressure reducer) that applies back pressure during dispersion, and the crude dispersion was subjected to a dispersion process at a pressure of 100 MPa. Specifically, the CNTs were dispersed by applying shear force to the crude dispersion while applying back pressure. The dispersion process was carried out for 10 minutes while the dispersion flowing out of the high-pressure homogenizer was returned to the high-pressure homogenizer. Dispersion B was obtained by the above-mentioned dispersion process. The obtained dispersion B was impregnated into carbon paper (manufactured by Toray, product name "TGP-H-090", porosity: 78%), and the dispersion B-impregnated carbon paper was washed with isopropyl alcohol (IPA) and pure water in that order to remove the dispersant SDBS. Then, it was vacuum-dried at 80°C for 24 hours to obtain a carbon sheet. The obtained carbon sheet was evaluated for the same items, and the results are shown in Table 1. Furthermore, a metal oxide-supporting sheet was produced by carrying out the same treatment as in Example 1, and the average diameter of the metal oxide was measured. The results are shown in Table 1.
[0095] (Comparative Example 1-1) A carbon sheet was prepared in the same manner as in Example 1, except that no spacer particles were added, and the same items were evaluated. The results are shown in Table 1. Furthermore, a metal oxide-supporting sheet was produced by carrying out the same treatment as in Example 1, and the metal oxide was observed, but no metal oxide was formed inside the sheet.
[0096] [Table 1]
[0097] (Example 2-1) CNTs (manufactured by Zeon Nano Technology, product name "ZEONNANO (registered trademark) SG101", SGCNTs mainly containing single-walled CNTs, average diameter 3.3 nm, nitrogen adsorption specific surface area: 1,000 m) were added to 20 mL of isopropyl alcohol (IPA). 2 20 mg of CNTs (at least 100 μm / g) was added and dispersed for 20 minutes in a bath-type ultrasonic disperser to obtain a dispersion. The average bundle diameter of CNTs in the obtained dispersion was 100 μm. The obtained dispersion was placed in a reduced pressure filtration device equipped with a membrane filter and filtered under a condition of 0.09 MPa, and the membrane filter was peeled off to obtain a carbon sheet. The porosity, electromagnetic wave absorption properties, and infrared absorption properties of the obtained carbon sheet were measured and evaluated. The results are shown in Table 2. The thickness and density of the obtained carbon sheet were measured and found to be 3,390 μm in thickness and 0.1 g / cm in density. 3 It was.
[0098] (Example 2-2) A carbon sheet was produced in the same manner as in Example 2-1, except that the average bundle diameter of CNTs in the obtained dispersion was changed from 100 μm to 1 μm by changing the dispersion treatment time from 20 minutes to 40 minutes, and the same items were measured and evaluated. The results are shown in Table 2. The thickness and density of the obtained carbon sheet were measured and found to be 1870 μm and 0.4 g / cm. 3 It was.
[0099] (Example 2-3) A carbon sheet was produced in the same manner as in Example 2-1, except that the average bundle diameter of CNTs in the obtained dispersion was changed from 100 μm to 0.5 μm by changing the dispersion treatment time from 20 minutes to 60 minutes, and the same items were measured and evaluated. The results are shown in Table 2. The thickness and density of the obtained carbon sheet were measured and found to be 850 μm and 0.7 g / cm. 3 It was.
[0100] (Comparative Example 2-1) Add 200 mg of sodium dodecyl sulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., "Sodium Dodecyl Sulfate") as a surfactant to 20 mL of pure water, and CNT (manufactured by Zeon Nano Technology, Inc., product name "ZEONNANO (registered trademark) SG101", SGCNT mainly containing single-walled CNT, average diameter: 3.3 nm, nitrogen adsorption specific surface area: 1,000 m 2 20 mg of CNTs (w / g or more) were added and dispersed for 60 minutes in a bath-type ultrasonic disperser to obtain a dispersion. The average bundle diameter of CNTs in the obtained dispersion was 0.05 μm. The obtained dispersion was placed in a reduced pressure filtration device equipped with a membrane filter and filtered under a condition of 0.09 MPa, and the membrane filter was peeled off to obtain a carbon sheet. The porosity, electromagnetic wave absorption properties, and infrared absorption properties of the obtained carbon sheet were measured and evaluated. The results are shown in Table 2. The thickness and density of the obtained carbon sheet were measured and found to be 102 μm in thickness and 1.0 g / cm in density. 3 It was.
[0101] [Table 2]
[0102] From Table 1, the carbon sheets of Examples 1-1 to 1-4, which contain carbon nanotubes and have a porosity of 5% or more and 90% or less, are self-supporting and have an air permeability of 5 cc / cm 2 / s or more 60cc / cm 2 / s or less, and further, when metal oxide is loaded, loaded particles can be observed inside the sheet, indicating that the material is easy to handle and process, and is also capable of loading different materials into its interior when used as a carrier for different materials.
[0103] Furthermore, in Comparative Example 1-1, in which the porosity is below the specified range, the air permeability is not within the above-mentioned range compared to Examples 1-1 to 1-4, and further, when a metal oxide is supported on the carbon sheet, no supported particles are observed inside the sheet, indicating that the performance of supporting heterogeneous materials inside the carbon sheet is inferior.
[0104] From Table 2, it can be seen that the carbon sheets of Examples 2-1 to 2-3, which contain carbon nanotubes and have a porosity of 30% or more and 95% or less, have excellent electromagnetic wave absorption properties and infrared absorption properties.
[0105] Also, it is understood that the carbon sheet of Comparative Example 2-1, in which the porosity was not within the predetermined range, was inferior in electromagnetic wave absorption properties and infrared absorption properties to the carbon sheets of Examples 2-1 to 2-3. [Industrial Applicability]
[0106] The carbon sheet of the present invention can provide a material that is excellent in handleability and processability, and is capable of supporting a different material to its inside when used as a support for a different material. Furthermore, the carbon sheet of the present invention can provide a material that has excellent electromagnetic wave absorption properties and infrared ray absorption properties.
Claims
1. A method for producing a carbon sheet having a structure in which only a plurality of carbon nanotubes are entangled and having a porosity of 5% or more and 90% or less, comprising the steps of: A primary sheet preparation step of removing the solvent from a dispersion containing carbon nanotubes, spacer particles, and a solvent to obtain a primary sheet; a spacer particle removing step of removing the spacer particles from the primary sheet by applying a physical impact to the primary sheet or by heat treating the primary sheet; Equipped with the spacer particles are dispersed in the dispersion liquid and are removable in the spacer particle removal step; The carbon nanotubes have an aspect ratio of more than 10.
2. A method for producing a carbon sheet comprising a porous substrate made of carbon and carbon nanotubes attached to the porous substrate, the carbon sheet having a porosity of 5% or more and 90% or less, comprising the steps of: A dispersion impregnation step of impregnating a carbon porous substrate with a dispersion containing carbon nanotubes and a solvent to obtain a dispersion-impregnated porous substrate; a solvent removal step of removing the solvent from the dispersion-impregnated porous substrate; Equipped with The carbon porous substrate is in the form of a sheet, The porosity of the carbon porous substrate is 5% or more and 90% or less, The carbon nanotubes have an aspect ratio of more than 10.
3. The method for producing a carbon sheet according to claim 1 or 2, wherein the carbon nanotubes are single-walled carbon nanotubes.
4. The carbon nanotube has a nitrogen adsorption specific surface area of 600 m 2 The method for producing a carbon sheet according to any one of claims 1 to 3, wherein the surface roughness is 1 / g or more.
Citation Information
Patent Citations
Large-scale manufacturing of nanostructured materials
JP2009506973A
High-density carbon nanotube assembly and method for producing the same
JP2010105909A
Infrared-absorbing heat-conductive member
JP2012188305A
Transparent electroconductive laminate, method for producing the same, and electronic paper and touch panel obtained by using the same
JP2014060158A
CNT rubber composition and CNT molded body
JP2016175836A